Chronic pain is a risk factor for incident Alzheimer’s disease: a nationwide propensity-matched cohort using administrative data - Bornier, Nadège; Mulliez, Aurélien; Chenaf, Chouki; Elyn, Antoine; Teixeira, Sarah; Authier, Nicolas; Bertin, Célian; Kerckhove, Nicolas (Frontiers in Aging Neuroscience, 2023)
Chronic pain (CP) is one of the most disabling conditions in the elderly and seems to be a risk factor for the development of Alzheimer’s disease and related dementias (ADRD). Only one study, using national administrative health databases, assessed and demonstrated that chronic pain (all types of pain) was a risk factor for dementia, but without assessing the impact of pain medications. To assess the impact of all types of chronic pain and the long-term use of pain medications on the person-years incidence of ADRD, a retrospective nationwide healthcare administrative data study was performed using the national inter-regime health insurance information system (SNIIRAM) to the French national health data system (SNDS). Incident people >50 years old with chronic pain, defined by at least 6-months duration analgesics treatment or by a diagnosis/long-term illness of chronic pain between 2006 and 2010, were included. Chronic pain individuals were matched with non-CP individuals by a propensity score. Individuals were followed up from 9 to 13 years to identify occurrences of ADRD from 2006. Among 64,496 French individuals, the incidence of ADRD was higher in the chronic pain population than control (1.13% vs. 0.95%, p<0.001). Chronic pain increases the risk of ADRD (HR = 1.23) and the long-term use of opioids and non-opioid analgesics were related to the presence of ADRD (OR = 1.90 and 2.80). The incidence of ADRD was higher for women and increased significantly with age. Our study highlights the importance of prevention, diagnosis, and management of chronic pain in elderly to reduce the risk of development and/or worsening of dementia.